Telehealth for the study of palliative care communication: opportunities, methodological challenges, and recommendations - Elise C. Tarbi; Susanna L. Schuler; Natalie Ambrose; Rebecca N. Hutchinson; Maija Reblin; Katharine L. Cheung (BMC Palliative Care)
Abstract Background While telehealth may offer promise for accessible, efficient palliative care delivery, leveraging telehealth technologies as an opportunity to better understand and advance the science of palliative care communication has been less well explored. Without identifying solutions to overcome challenges to conducting research in the virtual environment, we are unable to conduct the foundational work to offer evidence-based recommendations for high-quality telehealth, particularly in the context of palliative care. Our objective is to highlight methodological challenges in the use of telehealth for the study of palliative care communication and share lessons learned from using these methods. Methods This paper is the result of a reflective process and experience across three ongoing observational communication research studies focused on the use of telehealth during serious illness. These research datasets have been collected from multiple sites and represent rural and urban telehealth palliative care consultations for patients receiving dialysis (n = 34), patients with cancer (n = 13), and seriously ill, home-bound patients (n = 9). We illustrate challenges, insights, and recommendations with case studies from these studies. Results We identify key challenges, and offer recommendations to address them, in telehealth palliative care communication research. Key insights fall within three themes: 1) addressing accessibility barriers to enrollment in telehealth research; 2) technical considerations regarding how software and hardware choices have implications for data collection and analysis; and 3) ethical considerations regarding the nuances of consent and privacy in telehealth encounters. Conclusions Overall, our approach demonstrates possibilities for the use of telehealth to study palliative care communication and provides a “how-to” example for unique telehealth considerations from data collection through analysis. These strategies can facilitate success with large-scale health communication research studies in the telehealth context.